Efeitos do fundo de desenvolvimento da educação básica e valorização dos profissionais da educação - FUNDEB na educação infantil de Medianeira - Paraná - Lima, Ezequiel de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research analyzes the purposes of the Fund for the Development of Basic Education and Valorization of Education Professionals in early childhood education in the city of Medianeira, State of Parana. The motivation to perform the search was related to the desire to understand the relationship and the influence of public policy education funding and the effects on education. The study was developed from archival work on the administrative acts of the municipality of Medianeira, related to early childhood education, as budget law, multi-year plan, municipal laws positions and salaries of early childhood professionals, as well mapping of quantitative data on early childhood education, and funding after Fundeb. These data were analyzed with a focus in the context of practice, the policy cycle. The theoretical and methodological approach, included researchers from the field of education and social sciences show the historical about the legal and Brazilian construction of the rights of children up to five years, mainly, after the Federal Constitution of 1998 and subsequent infra-laws, in the formation and organization of the field of early childhood education as part of basic education, was key to better understanding of educational policies in the context of practice. The effects revealed by the survey showed that there was: decreased deficit of places in early childhood education, but with difficulties to achieve the goal of the NAP 2014, enrolling 50% of children in day care centers; increased spending on early childhood education, more intensely from 2010, driven by investments in construction of kindergartens and increase in professional staff; creation of post of child educator with updating and equalization of salaries to other public school teachers. Finally, aspects were observed related: the Fundeb Council in the municipality, which highlighted the need for more dynamic performance in order to influence the planning; and the...

Esta pesquisa analisou efeitos do Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação na educação infantil do município de Medianeira, Estado do Paraná. A motivação para realizar a pesquisa esteve relacionada ao desejo de compreender a relação e a influência entre políticas públicas de financiamento da educação e os efeitos na educação. O estudo desenvolveu-se a partir de levantamento documental sobre os atos administrativos do município de Medianeira, relacionados à educação infantil, como lei orçamentária, plano plurianual, leis municipais de cargos e salários dos profissionais da educação infantil, bem como levantamento de dados quantitativos e financiamento da educação infantil após o Fundeb. O conjunto desses dados foi analisado com foco no contexto da prática, do ciclo de políticas. O percurso teórico-metodológico, contou com pesquisadores da área da educação e das ciências sociais A reconstituição histórica acerca da construção jurídico-brasileira dos direitos das crianças de zero a cinco anos, principalmente, após a Constituição Federal de 1998 e leis infraconstitucionais subsequentes, na formação e organização do campo da educação infantil como integrante da educação básica, foi fundamental para melhor compreensão das políticas educacionais no contexto da prática. Os efeitos revelados pela pesquisa demonstraram que houve: diminuição do déficit de vagas da educação infantil, mas com dificuldades de se atingir a meta do PNE 2014, de matricular 50% das crianças nas creches; aumento de gastos com a educação infantil, de forma mais intensa a partir de 2010, motivados por investimentos em construção de creches e aumento no quadro de profissionais; criação de cargo de educador infantil com atualização e equiparação dos vencimentos aos demais professores da rede municipal. Finalmente, foram observados aspectos...
Keywords: FUNDEF; Educação de crianças; Educação - Financiamento; Politicas publicas; Public policy